Utilization of Maternal Health Care Services in Kihun Village Development Committee of Tanahun District of Nepal - Pokhrel, B.R.; Parajuli, S.B.; Khatiwada, S.; Adhikari, C. (Birat Journal of Health Sciences, 2017)
Introduction Nepal had significant improvement to reduce the maternal mortality ratio. Still, the maternal deaths are common in rural areas. The proper utilization of maternal health care services is important to reduce maternal death in Nepal. Objective This study was conducted to know current maternal health care service utilization at Kihun Village Development Committee (VDC) of Tanahu District. Methodology A community based cross- sectional study was conducted from st th 1 Nov 2014 to 30 Dec 2014 among 570 household of Kihun VDC. The pretested semi-strutured questionnaire was used to collect the required information. The obtained data was enter into Microsoft excel analyzed. Results The majority (65%) of the family was nuclear. Majority (90.90%) had Hindu as a common religion. The major occupation was agriculture (68.95%). Age of marriage before 18 years was 44.70% and pregnancy below 18 years was 25.5%. The knowledge of ante natal care (ANC) check up was reported from 96.3% but only 93.20 % went for ANC check up. Almost 41% had 4 times ANC visit as suggested by world health organization (WHO). Majority (69.40% ) had home delivery and 56.8% of them, family members were involved to conduct such delivery. Though 31.20% were aware about post natal care (PNC) visit but only 22% had visited for PNC. Conclusion The ANC and PNC care practices were not up to the mark. For improvement of maternal health, we need to improve maternal health care service utilization. Birat Journal of Health Sciences 2016 1(1): 56-60